Perancangan Kontrol Dan Monitoring Level Ketinggian Air Di Waduk Bagian Hulu Untuk Meningkatkan Efektifitas Kinerja PLTA Koto Panjang - Maidi Rizki; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Activity monitoring water levels in reservoirs hydropower Koto Panjang are generally still done conventionally, that is reading of a sign of watershed mounted on the reservoir by way of a return of the power house to a reservoir which on avarage carried done three times a day, because of that is needed design control and monitoring level of water level by using ultrasonic sensor which is controlled from long distance 50 cm minimally until 10 m. The result of reading sensor are sent to microcontroller Arduino Uno for processed and sent by HT and displayed in PC. For displaying the data which received in monitor screen use software of LabView 2012. From the result sensor testing MB7366 able controlling the water level with error presentation 0.011% which is compared with a sign of watershed conventionally in reservoir and added with high time efficiency. From the result of comparison reading water elevation, reading from ultrasonic sensor can improve plant performance 0.03%.Keywords : Ultrasonic Sensor, Arduino Uno, LabView